![image](https://tex.z-dn.net/?f=1%29%5C%3B%5Csqrt%7Bx%5E2-3x%2B2%7D%3E2x-5%5C%5CO.D.3.%3A%5C%3Bx%5E2-3x%2B2%5Cgeq0%5C%5Cx%5E2-3x%2B2%3D0%5C%5CD%3D9-4%5Ccdot2%3D1%5C%5Cx_1%3D2%2C%5C%3Bx_2%3D1%5C%5C%28x-1%29%28x-2%29%5Cgeq0%5CRightarrow+x%5Cin%28-%5Cinfty%3B1%5D%5Ccup%5B2%3B%5C%3B%2B%5Cinfty%29%29%5C%5Cx%5E2-3x%2B2%3E%282x-5%29%5E2%5C%5Cx%5E2-3x%2B2%3E4x%5E2-20x%2B25%5C%5C-3x%5E2%2B17x-23%3E0%5C%5C3x%5E2-17x%2B23%3C0%5C%5C3x%5E2-17x%2B23%3D0%5C%5CD%3D289-4%5Ccdot3%5Ccdot23%3D289-276%3D13%5C%5Cx_1%3D%5Cfrac%7B17%2B%5Csqrt%7B13%7D%7D6%2C%5C%3Bx_2%3D%5Cfrac%7B17-%5Csqrt%7B13%7D%7D6%5C%5Cc%5C%3BO.D.3.%3A%5C%3Bx%5Cin%28-%5Cinfty%3B%5C%3B1%5D%5Ccup%5Cleft%5B2%2C%5C%3B%5Cfrac%7B17%2B%5Csqrt%7B13%7D%7D6%5Cright%29)
2x-5\\O.D.3.:\;x^2-3x+2\geq0\\x^2-3x+2=0\\D=9-4\cdot2=1\\x_1=2,\;x_2=1\\(x-1)(x-2)\geq0\Rightarrow x\in(-\infty;1]\cup[2;\;+\infty))\\x^2-3x+2>(2x-5)^2\\x^2-3x+2>4x^2-20x+25\\-3x^2+17x-23>0\\3x^2-17x+23<0\\3x^2-17x+23=0\\D=289-4\cdot3\cdot23=289-276=13\\x_1=\frac{17+\sqrt{13}}6,\;x_2=\frac{17-\sqrt{13}}6\\c\;O.D.3.:\;x\in(-\infty;\;1]\cup\left[2,\;\frac{17+\sqrt{13}}6\right)" alt="1)\;\sqrt{x^2-3x+2}>2x-5\\O.D.3.:\;x^2-3x+2\geq0\\x^2-3x+2=0\\D=9-4\cdot2=1\\x_1=2,\;x_2=1\\(x-1)(x-2)\geq0\Rightarrow x\in(-\infty;1]\cup[2;\;+\infty))\\x^2-3x+2>(2x-5)^2\\x^2-3x+2>4x^2-20x+25\\-3x^2+17x-23>0\\3x^2-17x+23<0\\3x^2-17x+23=0\\D=289-4\cdot3\cdot23=289-276=13\\x_1=\frac{17+\sqrt{13}}6,\;x_2=\frac{17-\sqrt{13}}6\\c\;O.D.3.:\;x\in(-\infty;\;1]\cup\left[2,\;\frac{17+\sqrt{13}}6\right)" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=2%29%5C%3B%5Csqrt%7B-x%5E2%2B6x-5%7D%3E8-2x%5C%5CO.D.3.%3A%5C%3B-x%5E2%2B6x-5%5Cgeq0%5C%5Cx%5E2-6x%2B5%5Cleq0%5C%5Cx%5E2-6x%2B5%3D0%5C%5CD%3D36-4%5Ccdot5%3D16%5C%5Cx_1%3D5%2C%5C%3Bx_2%3D1%5C%5C%28x-1%29%28x-5%29%5Cleq0%5CRightarrow+x%5Cin%5B1%3B5%5D%5C%5C%5Csqrt%7B-x%5E2%2B6x-5%7D%3E8-2x%5C%5C-x%5E2%2B6x-5%3E%288-2x%29%5E2%5C%5C-x%5E2%2B6x-5%3E64-32x%2B4x%5E2%5C%5C-5x%5E2%2B38x-69%3E0%5C%5C5x%5E2-38x%2B69%3C0%5C%5C5x%5E2-38x%2B69%3D0%5C%5CD%3D1444-4%5Ccdot5%5Ccdot69%3D64%5C%5Cx_1%3D3%2C%5C%3Bx_2%3D4%2C6%5C%5C5%28x-3%29%28x-4%2C6%29%3C0%5CRightarrow+x%5Cin%283%3B%5C%3B4%2C6%29%5C%5Cc%5C%3BO.D.3.%3A%5C%3Bx%5Cin%283%3B%5C%3B4%2C6%29)
8-2x\\O.D.3.:\;-x^2+6x-5\geq0\\x^2-6x+5\leq0\\x^2-6x+5=0\\D=36-4\cdot5=16\\x_1=5,\;x_2=1\\(x-1)(x-5)\leq0\Rightarrow x\in[1;5]\\\sqrt{-x^2+6x-5}>8-2x\\-x^2+6x-5>(8-2x)^2\\-x^2+6x-5>64-32x+4x^2\\-5x^2+38x-69>0\\5x^2-38x+69<0\\5x^2-38x+69=0\\D=1444-4\cdot5\cdot69=64\\x_1=3,\;x_2=4,6\\5(x-3)(x-4,6)<0\Rightarrow x\in(3;\;4,6)\\c\;O.D.3.:\;x\in(3;\;4,6)" alt="2)\;\sqrt{-x^2+6x-5}>8-2x\\O.D.3.:\;-x^2+6x-5\geq0\\x^2-6x+5\leq0\\x^2-6x+5=0\\D=36-4\cdot5=16\\x_1=5,\;x_2=1\\(x-1)(x-5)\leq0\Rightarrow x\in[1;5]\\\sqrt{-x^2+6x-5}>8-2x\\-x^2+6x-5>(8-2x)^2\\-x^2+6x-5>64-32x+4x^2\\-5x^2+38x-69>0\\5x^2-38x+69<0\\5x^2-38x+69=0\\D=1444-4\cdot5\cdot69=64\\x_1=3,\;x_2=4,6\\5(x-3)(x-4,6)<0\Rightarrow x\in(3;\;4,6)\\c\;O.D.3.:\;x\in(3;\;4,6)" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=3%29%5C%3Bx%5E2%3Ex%282%2B%5Csqrt%7B12-2x-x%5E2%7D%29%5C%5CO.D.3.%3A%5C%3B12-2x-x%5E2%5Cgeq0%5C%5Cx%5E2%2B2x-12%5Cleq0%5C%5Cx%5E2%2B2x-12%3D0%5C%5CD%3D4%2B4%5Ccdot12%3D52%3D%282%5Csqrt%7B13%7D%29%5E2%5C%5Cx_1%3D-1-%5Csqrt%7B13%7D%2C%5C%3Bx_2%3D-1%2B%5Csqrt%7B13%7D%5C%5C%28x%2B1%2B%5Csqrt%7B13%7D%29%28x%2B1-%5Csqrt%7B13%7D%29%5Cleq0%5CRightarrow+x%5Cin%5B-1-%5Csqrt%7B13%7D%3B%5C%3B-1%2B%5Csqrt%7B13%7D%5D)
x(2+\sqrt{12-2x-x^2})\\O.D.3.:\;12-2x-x^2\geq0\\x^2+2x-12\leq0\\x^2+2x-12=0\\D=4+4\cdot12=52=(2\sqrt{13})^2\\x_1=-1-\sqrt{13},\;x_2=-1+\sqrt{13}\\(x+1+\sqrt{13})(x+1-\sqrt{13})\leq0\Rightarrow x\in[-1-\sqrt{13};\;-1+\sqrt{13}]" alt="3)\;x^2>x(2+\sqrt{12-2x-x^2})\\O.D.3.:\;12-2x-x^2\geq0\\x^2+2x-12\leq0\\x^2+2x-12=0\\D=4+4\cdot12=52=(2\sqrt{13})^2\\x_1=-1-\sqrt{13},\;x_2=-1+\sqrt{13}\\(x+1+\sqrt{13})(x+1-\sqrt{13})\leq0\Rightarrow x\in[-1-\sqrt{13};\;-1+\sqrt{13}]" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=%5C%5Cx%5E2%3E2x%2Bx%5Csqrt%7B12-2x-x%5E2%7D%5C%5C%28x%5E2-2x%29%5E2%3Ex%5E2%2812-2x-x%5E2%29%5C%5Cx%5E4-4x%5E3%2B4x%5E2%3E12x%5E2-2x%5E3-x%5E4%5C%5C2x%5E4-2x%5E3-8x%5E2%3E0%5C%5C2x%5E2%28x%5E2-x-4%29%3E0%5C%5Cx%5E2%5Cleft%28x-%5Cfrac%7B1-%5Csqrt%7B17%7D%7D2%5Cright%29%5Cleft%28x-%5Cfrac%7B1%2B%5Csqrt%7B17%7D%7D2%5Cright%29%5CRightarrow+x%5Cin%28-%5Cinfty%3B0%29%5Ccup%5Cleft%28%5Cfrac%7B1%2B%5Csqrt%7B17%7D%7D2%3B%5C%3B%2B%5Cinfty%5Cright%29)
2x+x\sqrt{12-2x-x^2}\\(x^2-2x)^2>x^2(12-2x-x^2)\\x^4-4x^3+4x^2>12x^2-2x^3-x^4\\2x^4-2x^3-8x^2>0\\2x^2(x^2-x-4)>0\\x^2\left(x-\frac{1-\sqrt{17}}2\right)\left(x-\frac{1+\sqrt{17}}2\right)\Rightarrow x\in(-\infty;0)\cup\left(\frac{1+\sqrt{17}}2;\;+\infty\right)" alt="\\x^2>2x+x\sqrt{12-2x-x^2}\\(x^2-2x)^2>x^2(12-2x-x^2)\\x^4-4x^3+4x^2>12x^2-2x^3-x^4\\2x^4-2x^3-8x^2>0\\2x^2(x^2-x-4)>0\\x^2\left(x-\frac{1-\sqrt{17}}2\right)\left(x-\frac{1+\sqrt{17}}2\right)\Rightarrow x\in(-\infty;0)\cup\left(\frac{1+\sqrt{17}}2;\;+\infty\right)" align="absmiddle" class="latex-formula">